Scanning Electron Microscopy Analysis and Energy Dispersion X-ray Microanalysis to Evaluate the Effects of Decontamination Chemicals and Heat Sterilization on Implant Surgical Drills: Zirconia vs. Steel - Antonio Scarano (Applied Sciences, 2019)
Background: Drills are an indispensable tool for dental implant surgery. Today, there are ceramic zirconium dioxide and metal alloy drills available. Osteotomy drills are critical instruments since they come in contact with blood and saliva. Furthermore, they are reusable and should be cleaned and sterilized between uses. Depending on the material, sterilizing agents and protocols can alter the surface and sharpness of implant drills. The hypothesis is that cleaning and sterilization procedures can affect the surface structure of the drills and consequently reduce their cutting efficiency. Methods: Eighteen zirconia ceramic drills and eighteen metal alloy drills were evaluated. Within the scope of this study, the drills were not used to prepare implant sites. They were immersed for 10 min in human blood taken from volunteer subjects and then separately exposed to 50 cycles of cleansing with 6% hydrogen peroxide, cold sterilization with glutaraldehyde 2%, and autoclave heat sterilization. Scanning Electron Microscopy (SEM) and energy dispersion X-ray (EDX) microanalysis were conducted before and after each cycle and was used to evaluate the drill surfaces for alterations. Results: After exposure to the cleansing agents used in this study, alterations were seen in the steel drills compared to zirconia. Conclusions: The chemical sterilization products used in this study cause corrosion of the metal drills and reduce their sharpness. It was observed that the cycles of steam sterilization did not affect any of the drills. Zirconia drill surfaces remained stable.